(untitled) (Proceedings of International Educators Conference, 2024)
In this article, when studying the thermal resistance of lavandon-proliot diodes, an increase in the power of microwave generators in the LTD and the expansion of the operating frequency range necessitated a complete and accurate calculation of a number of characteristics of the LTD. Based on the thermal properties of the diode structures, the generation parameters in the LTD are determined; therefore, it is necessary to take into account the thermal conductivity of the semiconductor material in breakdown modes with a high current density